Estructuración del proceso para mejorar la calidad de la prestación del servicio al cliente en la empresa ASINFO Asesores Informáticos S.C. ubicada en el norte de la ciudad de Quito - Changoluisa Pabón, Jeanneth de Marillac (2010)
The research topic has significant relevance, since currently the IT market is seen from a perspective only benefit and no processes to provide greater security and reliability to customers in terms of service delivery takes, but in the present work determines the need for these businesses are in service and attention, because customers are the foundation of any business yl most companies in the country has chosen to purchase this type of services that facilitate the daily processes thereof.